ANALISIS PENGGUNAAN GADGET TERHADAP MOTIVASI BELAJAR PADA MATERI IKLAN DI KELAS IV SDN 1 CIGARUKGAK - Melly Lailatul Munawwaroh; Rita Kusumah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Melly Lailatul Munawwaroh (206223031), Analysis of Gadget Usage on Learning Motivation in Advertising Material in Class IV of SDN I Cigarukgak, Study Program of Primary School Teacher Education (PGSD), 2025. In this era of globalization, all groups from children, teenagers to adults, are familiar with advanced tools or technologies that can facilitate and lighten human work. The advanced technology in question is gadgets. However, the use of gadgets by students has an impact on their learning motivation, both negative and positive effects. This research aims to describe how the use of gadgets affects learning motivation in advertising material in class IV of SDN 1 Cigarukgak. This research uses qualitative research methods. Qualitative research is intended to reveal phenomena comprehensively and according to the context or as it is through data collection in a natural setting as a direct source with the key instruments of the research itself. The subjects in this study are the homeroom teachers and the fourth-grade students at SDN 1 Cigarukgak. The object of research is the focal point in a study. The object of this research is the implementation of gadget usage as a learning medium and how its use impacts the learning motivation in the subjects of the fourth-grade students at SDN 1 Cigarukgak. Therefore, this research employs data collection techniques that include observation, interviews, and documentation.